(untitled) - Hons, Miloš (Aura musica, 2020)
In the 1960s, there was a radical break with tradition in the work of leading Czech composers Jan Rychlík, Jan Klusák, Marek Kopelent and Luboš Fišer. They began to apply the principles and techniques of serialism and punctualism, effects in the field of timbre music, inspired by the poetry of Dadaism, symbolism, etc. content. This work, which falls under the stylistic name New Music of the 1960s, belongs today to an almost forgotten history, but at the same time demonstrates the high level of Czech choral art of that time.